Evaluation of oral microbiota in undernourished and eutrophic children using checkerboard DNA-DNA hybridization. (December 2016) - Testa, M.; Erbiti, S.; Delgado, A.; Cardenas, I.L.
Abstract: The aim of this study was to evaluate the relationship among nutritional status, gingival health and the composition of oral microbiota in children of a public school from a very poor area of San Miguel de Tucuman. Forty-five children ranging in age from 6 to 14 years old, 13 males and 32 females were studied. Twenty of these children were undernourished (Lejarraga-Morasso Table) and twenty-five were eutrophic. A clinical study that included DMF and dmf indexes, Löe Silness Plaque Index and bleeding on probing was performed. For microbiological study, saliva samples without stimulation were taken; aliquots of them were immediately placed in TAE buffer pH 7.6, adding NaOH (N and keeping at -70 °C until processed by checkerboard DNA-DNA hybridization method to check the presence of 40 oral microorganism species. Positive bleeding on probing was present in more than 80% of children, without significant differences between eutrophic and undernourished groups. Same result were obtain for the other clinical indexes (p > 0.05, Two Way ANOVA). Significant differences were found for some oral microorganism species, with a higher percentage of undernourished children harboring them. That was the case of S. gordonii (p < 0.05), Capnocitophaga gingivalis and C. ochraceae (p < 0.01 and p < 0.10, respectively), F. nucleatum ss nucleatum (p < 0.05), P. nigrescens (p < 0.10), Campylobacter gracilis (p < 0, 05), and T. denticola (p < 0.10, multiple logistic regression). Significant differences were also found between children groups for E. saborreum (p < 0.001), P. acnes (p < 0.10), G. morbillorum (p < 0.05) and L. buccalis (p < 0.10). Gingivitis and bleeding on probing would not be related to nutritional status in the groups of children studied. There were significant differences for the presence of some of the main periodontal pathogen species between eutrophic and undernourished children. It would be important to study the meaning of significant differences found for the other microorganisms more deeply. Highlights: Relationship among nutritional status, gingival health and the composition of oral microbiota was evaluated, using DNA-DNA hybridization method. Significant differences for some oral microorganisms were found. There were significant differences for the presence of some periodontal pathogens between eutrophic and undernourished children.